Necrotizing Infundibular Crystalline Folliculitis: A Case Report of an Exceptional Lesion of Unknown Etiology - Nikolina Saxer-Sekulic; Brigitte Vion-Gauthey; Gürkan Kaya (MDPI AG, 2014)
Necrotizing infundibular crystalline folliculitis is a rare follicular lesion of which the etiology is not well understood. Here we describe the case of a 71-year-old male patient presenting with multiple hyperkeratotic lesions localized on the forehead. Histopathological analysis of one of the lesions revealed a follicular invagination containing cellular debris and keratin lamellae containing filamentous mucinous material and numerous crystals birefringent in polarized light microscopy. © 2014 S. Karger AG, Basel